PENGARUH KREDIT CEPAT AMAN (KCA) TERHADAP PENDAPATAN NASABAH (Studi Pada Nasabah KCA PT. Pegadaian Cabang Moyo Hilir) - Nining Sudiyarti; Bagas Irwansyah; Rosyidah Rachman (Pusat Riset dan Publikasi, 2022)
This study aims to determine the effect of fast and secure credit (KCA) on the income of customers of PT. Moyo Hilir Service Unit Pegadaian. This type of research is associative research to determine the influence or relationship between two or more variables. The variables that will be studied in this study are fast and secure credit Loans (KCA) as the independent variable (free), and Customer Income as the dependent variable (tied). This study uses quantitative data types obtained from primary sources, namely all fast and secure credit (KCA) customers at PT. Pegadaian Service Unit Moyo Hilir January-June 2022 totaling 51 people. Data collection was carried out using a questionnaire distributed to respondents. The data that has been collected is processed with the help of the SPSS program and studied using simple linear regression analysis techniques, partial parameter hypothesis testing (t test), and determination coefficient test (R2). The results of this study indicate that the granting of fast and secure credit (KCA) has a positive and significant effect on the income of PT. Moyo Hilir Service Unit Pegadaian. The variable ability of granting fast safe credit (KCA) in explaining variations in changes in customer income variables of PT. Pegadaian Service Unit of Moyo Hilir is 80.7%, while the remaining 19.3% is influenced by other variables outside this research model.